The effect of social media influencers on the consumption pattern of Business Economics students of the UPDEPP - Quinto, Angel Anne V.; De Leon, Patrick C. (Pampanga University of the Philippines Diliman Extension Program in Pampanga, 2025)
This study examined the effect of social media influencers on the consumption patterns of Business Economics students at UPDEPP for the Academic Year 2024-2025. The study used the theory of the consumer and the concept of network externality as elements of its framework. The needed data for the study were gathered through online and face-to-face surveys of 130 BE students. The study showed that most respondents discovered influencer content through social media algorithms (96.15%) and made purchases online (88.5%), mainly in fashion and beauty. Nearly 87% watched reviews before buying, yet 48.5% regretted their purchases, suggesting a gap between perceived and actual value. Additionally, respondents were neutral about the authenticity of endorsements, with an average Likert scale rating of 2.677 (neither agree nor disagree), indicating some skepticism. Influencer marketing also accounted for a greater variance in spending behavior than traditional channels. The study concludes that social media influencers significantly impact students' purchasing decisions, highlighting the need to address concerns about endorsement authenticity and post-purchase satisfaction, It recommends strengthening consumer protection measures and promoting consumer education to help students make more informed spending decisions, Future research should expand the demographic scope and explore the psychological effects of influencer marketing and social media algorithms.
Thesis (Business Economics) UPDEPP, 2025
Keywords: Consumer behavior .; Market surveys; Internet personalities